2014
DOI: 10.1128/iai.01739-14
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Burkholderia pseudomallei Type II Secretome Reveals Hydrolytic Enzymes, Novel Proteins, and the Deubiquitinase TssM

Abstract: bBurkholderia pseudomallei, the etiologic agent of melioidosis, is an opportunistic pathogen that harbors a wide array of secretion systems, including a type II secretion system (T2SS), three type III secretion systems (T3SS), and six type VI secretion systems (T6SS). The proteins exported by these systems provide B. pseudomallei with a growth advantage in vitro and in vivo, but relatively little is known about the full repertoire of exoproducts associated with each system. In this study, we constructed deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 61 publications
(90 reference statements)
1
54
0
Order By: Relevance
“…Interference with host immunity pathways is achieved in Bpmt infection by the deubiquitinase TssM (unrelated to the T6SS structural component of the same name), which inhibits NF-kB and type I interferon signaling [51,52]. TssM is a T2SS-dependent protein but is in fact encoded within the T6SS-5 cluster [53].…”
Section: Modulation Of the Inflammatory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Interference with host immunity pathways is achieved in Bpmt infection by the deubiquitinase TssM (unrelated to the T6SS structural component of the same name), which inhibits NF-kB and type I interferon signaling [51,52]. TssM is a T2SS-dependent protein but is in fact encoded within the T6SS-5 cluster [53].…”
Section: Modulation Of the Inflammatory Responsementioning
confidence: 99%
“…The evolved VgrG5, with unknown catalytic activity, is responsible for the fusion of host cell membranes leading to multinucleated giant cell formation[57,58]. The T6SS-5 cluster also encodes an autotransporter, BimA, involved in actin-mediated propulsion; and TssM, a T2SS-dependent effector that dampens NF-kB and type I interferon signaling[51,53,55]. II.…”
mentioning
confidence: 99%
“…The tssM gene is physically linked to both the T3SS-3 and T6SS-1 gene clusters and is co-regulated with T6SS-1, but neither system is involved in TssM export [71]. It has recently been shown that secretion of TssM is instead dependent on a functional type II secretion system (T2SS) [72]. When secreted inside macrophages, TssM interferes with the toll-like receptor (TLR) mediated NF-κB signaling pathways associated with innate immune responses [71].…”
Section: Other Secreted Proteinsmentioning
confidence: 99%
“…Second, the T2S system is commonly required for the secretion of several proteins in other species. For example, proteomic analyses of culture supernatants of L. pneumophila, V. cholerae, and Burkholderia pseudomallei indicate that more than 20 different proteins may be dependent on the T2S system for extracellular release (30,39,76). Future work will focus on identifying additional T2S substrates and determining their role in A. baumannii pathogenesis.…”
Section: Figmentioning
confidence: 99%